Clinical, Autonomic & Electrophysiological Features in Patients with Guillain Barre Syndrome in a Tertiary Care Hospital of Bangladesh - Jannat, Maftahul; Hannan, MA; Alam, Sheikh Mahbub; Islam, Md Rafiqul; Chowdhury, Amit Roy; Rahman, Md Habibur; Das, Saumitra; Hossain Patwary, AM Shafayet; Islam, Md Fakrul; Md Hasan Ali Masum, Abu Shams (Bangladesh Journal of Neuroscience, 2019)
Background: Guillain-Barre Syndrome (GBS) is the most common cause of acute flaccid paralysis in the adult population. It is an acute post infectious immune mediated peripheral neuropathy with a marked variation in pathology, clinical presentation and prognosis. Objective: The aim of the study were to evaluate clinical profile, to assess autonomic involvement & electrophysiological findings in adult patients with GBS. Methods: An observational, cross sectional study was carried out in the Department of Neurology, BSMMU, Dhaka from March, 2015 to September, 2017. Total 43 patients of GBS fulfilling the inclusion criteria were recruited as the study population. Detailed clinical examination, CSF study & nerve conduction study were done. Disability status was measured by Hughes functional grading scale. For autonomic assessment 35 adult healthy control were also included for comparison. Then following tests of autonomic nervous system were performed in both patient and control group 1) resting heart rate and heart rate on changing posture (30: 15 ratio) 2) supine blood pressure and blood pressure on changing posture 3) heart rate response to valsalva maneuver 4) heart rate response to deep breathing and E: I ratio 5) sphincter disturbance by symptoms questionnaire. Results: The mean age of patients was 35±12 years (range18 to 65 years) with slight male predominance (58.1%). Major clinical presentation was weakness of all 4 limbs followed by sensory complaints (44.2%). 7% of the patient had breathing difficulty and dysphagia. Only 4.7 % had diplopia. Among the symptoms of autonomic dysfunction most common symptoms was constipation (30.2 %) followed by palpitation (14%), urinary retention (7%), lightheadedness and urinary incontinence (4.7%). Cranial nerve palsy was present in 34.9% of cases among them facial palsy was found commonly (27.9%), followed by bulbar palsy (7%) and ophthalmoplegia (4.7%). One patient (2.3%) had both facial palsy and ophthalmoplegia. AIDP, AMAN and AMSAN subtypes comprised 32.6%, 37.2% and 20.9% of cases respectively. Regarding autonomic dysfunction variation of heart rate by different maneuver like posture change, deep breathing and valsalva maneuver was found commonly. 30:15 ratio was abnormal in majority of the patients (82.4%) followed by abnormal max-min HR/min on deep breathing (58.1%) and abnormal valsalva ratio (37.2%). Other abnormalities were postural hypotension (38.2%), sinus tachycardia (25.6%), hypertension (16.3%), hypotension (4.7%), and sinus arrhythmia (4.7%). Bowel bladder dysfunction was another autonomic dysfunction among them constipation 30%, urinary retention 7% and urinary incontinence 4.7% of cases. Conclusion: GBS can be presented with variable presentation including autonomic dysfunction. In this study common clinical presentation was limb weakness & different patterns of autonomic dysfunction was found in patients with GBS. Common electrophysiological subtype was AMAN. So in addition to clinical & electrophysiological analysis autonomic evaluation is essential in every patients with GBS as autonomic dysfunction is one of important cause of mortality. Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 57-62